SPEECH ACT IN BARACK OBAMA’S SPEECH - Peby Utami; Ibnu Iqbal; Farhan Najmi; Emeliya Sukma Dara Damanik (Universitas Galuh, 2022)
The purpose of this study is to analyze Barack Obama's usage of speech acts in speech